Understanding patients’ experiences of the wish to hasten death: an updated and expanded systematic review and meta-ethnography - Rodríguez-Prat, Andrea (BMJ Open, 2017)
OBJECTIVES: Patients with advanced disease sometimes express a wish to hasten death (WTHD). In 2012, we published a systematic review and meta-ethnography of qualitative studies examining the experience and meaning of this phenomenon. Since then, new studies eligible for inclusion have been reported, including in Europe, a region not previously featured, and specifically in countries with different legal frameworks for euthanasia and assisted suicide. The aim of the present study was to update our previous review by including new research and to conduct a new analysis of available data on this topic. SETTING: Eligible studies originated from Australia, Canada, China, Germany, The Netherlands, Switzerland, Thailand and USA. PARTICIPANTS: Studies of patients with life-threatening conditions that had expressed the WTHD. DESIGN: The search strategy combined subject terms with free-text searching of PubMed MEDLINE, Web of Science, CINAHL and PsycInfo. The qualitative synthesis followed the methodology described by Noblit and Hare, using the ‘adding to and revising the original’ model for updating a meta-ethnography, proposed by France et al. Quality assessment was done using the Critical Appraisal Skills Programme checklist. RESULTS: 14 studies involving 255 participants with life-threatening illnesses were identified. Five themes emerged from the analysis: suffering (overarching theme), reasons for and meanings and functions of the WTHD and the experience of a timeline towards dying and death. In the context of advanced disease, the WTHD emerges as a reaction to physical, psychological, social and existential suffering, all of which impacts on the patient’s sense of self, of dignity and meaning in life. CONCLUSIONS: The WTHD can hold different meanings for each individual—serving functions other than to communicate a genuine wish to die. Understanding the reasons for, and meanings and functions of, the WTHD is crucial for drawing up and implementing care plans to meet the needs of individual patients.